Menopausal hormone therapies and risk of colorectal cancer: a Swedish matched‐cohort study. Issue 11 (15th April 2021) - Liu, Qing; Simin, Johanna; Debelius, Justine; Fall, Katja; Sadr‐Azodi, Omid; Engstrand, Lars; Williams, Cecilia; Brusselaers, Nele
Summary: Background: Menopausal hormone therapy (MHT) has been associated with various malignancies. Aims: To investigate the association of various MHT regimens with the risk of colorectal cancer (CRC). Methods: All MHT ever‐users (n = 290 186) were included through the Swedish Prescribed Drug Registry, with a 1:3 group‐level matching to non‐users. Ever‐users were defined as women who received ≥1 dispensed prescription of systemic MHT during 2005‐2012 in Sweden. All CRC cases after drug initiation were extracted from the Swedish Cancer Registry. The association was assessed by multivariable conditional logistic and Cox regression models, presented as odds ratios (ORs) or hazard ratios (HRs) with 95% confidence intervals (CIs) considering different regimens, duration and age at treatment initiation. Results: Compared with non‐users, MHT users had an overall reduced odds for colon (OR = 0.67, 95% CI 0.63‐0.72) and rectal adenocarcinoma (OR = 0.66, 95% CI 0.60‐0.73), especially among women aged 40‐60 years. Current users of oestrogen‐only preparations (E‐MHT) showed a reduced odds (colon OR = 0.73, 95% CI 0.65‐0.82; rectal OR = 0.76, 95% CI 0.64‐0.90) compared to non‐users, particularly with oestradiol and oestriol. Past E‐MHT use showed stronger odds reductions (colon OR = 0.49, 95% CI 0.43‐0.56; rectal OR = 0.36, 95% CI 0.28‐0.45). Current use of oestrogen combined progestin therapy (EP‐MHT) indicated a less prominent odds reduction (colon adenocarcinoma OR 0.62, 95% CI 0.54‐0.72; rectal adenocarcinoma OR = 0.60, 95% CI 0.49‐0.74) than past users. Tibolone showed an increased risk of left‐sided colorectal adenocarcinoma. Oral and cutaneous MHT usage showed similar patterns. Conclusions: MHT use may decrease colorectal adenocarcinoma risk, for both E‐MHT and EP‐MHT, and especially in past users. Abstract : Menopausal hormone therapies and risk of colorectal cancer: a Swedish matched‐cohort study.